PENGARUH WAKTU TUNGGU PELAYANAN TERHADAP KEPUASAN PASIEN DI POLIKLINIK PENYAKIT DALAM RUMAH SAKIT MUHAMMADIYAH AHMAD DAHLAN KEDIRI - Alita Dewi Percunda; Adi Laksono, Hilmi Nur Widiyas Rama (Jurnal Kesehatan, 2024)
Customer satisfaction is the feeling of pleasure or disappointment that comes from comparing product performance with desired expectations. The general purpose of the study is to know how waiting times of service affect the patient's satisfaction. The study was done at the muhammadiyah hospital of ahmad dahlan kediri, using a quantitative method with a descriptive analysis and chi square test. The total sample number is 89 patients with sample proof samples. Data collection resources consist of primary and secondary data. The analyses used in this study include validity tests, religious tests, and chi square tests. The results of the test result are that patients expressing their time alone according to standard <60 minutes amount to 24 (27%) of respondents, while those not up to standard >60 minutes amount to 65 (73%). The characteristic satisfaction of the patient expressing satisfaction is 44 (50%), not 45 (50%). The study showed results that there was an influence between waiting times of service on the satisfaction of patients in polylinic disease inside the muhammadiyah hospital of ahmad dahlan keself. It was suggested to the hospital to continue to increase rapidly and alert to time distribution of time in the ministry.